Crystallization of the Ets1–Runx1–CBFβ–DNA complex formed on the TCRα gene enhancer - Shiina, Masaaki (International Union of Crystallography, 2014)
Gene transcription is regulated in part through the assembly of multiple transcription factors (TFs) on gene enhancers. To enable examination of the mechanism underlying the formation of these complexes and their response to a phosphorylation signal, two kinds of higher-order TF–DNA assemblies were crystallized composed of an unmodified or phosphorylated Ets1 fragment, a Runx1(L94K) fragment and a CBFβ fragment on the T-cell receptor (TCR) α gene enhancer. Within these complexes, the Ets1 and Runx1 fragments contain intrinsically disordered regulatory regions as well as their DNA-binding domains. Crystals of the complex containing unmodified Ets1 belonged to space group P2(1)2(1)2(1), with unit-cell parameters a = 78.7, b = 102.1, c = 195.0 Å, and diffracted X-rays to a resolution of 2.35 Å, and those containing phosphorylated Ets1 belonged to the same space group, with unit-cell parameters a = 78.6, b = 101.7, c = 194.7 Å, and diffracted X-rays to a similar resolution. To facilitate crystallization, a Runx1 residue involved in a hydrophobic patch that was predicted to be engaged in crystal packing based on the previously reported structures of Runx1-containing crystals was mutated.